Rethinking corporate community investment; an investigation into competencies, capacities and capabilities for tri-sector partnerships. - Tommy, Emmanuel Hindovei (2015)
Partnership is a way of work for many organisations- public, business and charities. Cross sector collaboration is a proven way of co-creating value. Organisations sometimes heighten the value creation effort by the three sectors - tri sector - working together. The sectors are different in goals and mode and inherently working together creates expectations which may not be met and lead to unproductiveness. the trend in seeking tri-sector partnerships is growing? It will take key competencies, capacities and capabilities to achieve success. This work endeavours to unravel what it takes for tri-sector partnerships to achieve their goals and objectives.